Impact of Single or Combined Genomic Alterations of TP53, MYC, and BCL2 on Survival of Patients With Diffuse Large B-Cell Lymphomas: A Retrospective Cohort Study. Issue 52 (December 2015) - Schiefer, Ana-Iris; Kornauth, Christoph; Simonitsch-Klupp, Ingrid; Skrabs, Cathrin; Masel, Eva Katharina; Streubel, Berthold; Vanura, Katrina; Walter, Karin; Migschitz, Brigitta; Stoiber, Dagmar; Sexl, Veronika; Raderer, Markus; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: MYC and BCL2 translocations as well as TP53 deletion/mutation are known risk factors in diffuse large B-cell lymphoma (DLBCL) but their interplay is not well understood. In this retrospective cohort study, we evaluated the combined prognostic impact of TP53 deletion and mutation status, MYC and BCL2 genomic breaks in tumor samples of 101 DLBCL patients. The cohort included 53 cases with MYC rearrangements ( MYC+ ). TP53 deletions/mutations ( TP53+ ) were found in 32 of 101 lymphomas and were equally distributed between MYC+ and MYC− cases (35.8% vs. 27.1%). TP53+ lymphomas had lower responses to treatment than TP53− (complete remission 34.4% vs. 60.9%; P = 0.01). TP53 alteration was the dominant independent prognostic factor in multivariate analysis ( P = 0.01). Overall survival (OS) varied considerably between subgroups with different genomic alterations: Patients with sole MYC translocation, and interestingly, with triple MYC+/BCL2+/TP53+ aberration had favorable outcomes (median OS not reached) similar to patients without genomic alterations (median OS 65 months). In contrast, patients with MYC+/BCL2+/TP53− double-hit lymphomas (DHL) (28 months), MYC+/BCL2−/TP53+ lymphomas (10 months) or sole TP53 mutation/deletion (12 months) had a poor median OS. Our findings demonstrate differences in OS of DLBCL patients depending on absence or presence of single or combined genetic alterations of MYC, BCL2, and TP53 . Cooccurrence of TP53 and BCL2 aberrations ameliorated the poor prognostic impact of single TP53+ or BCL2 + in MYC positive patients. This pilot study generates evidence for the complex interplay between the alterations of genetic pathways in DLBCL, which goes beyond the concept of DHL. The variable survival of DLBCL patients dependent on single or combined alterations in the TP53, MYC, and BCL2 genes indicates the need for comprehensive genomic diagnosis.